Growth problems of stellar black holes in early galaxies. Issue 1 (7th June 2018) - Orofino, M C; Ferrara, A; Gallerani, S
ABSTRACT: The nature of the seeds of the observed high-z supermassive black holes (SMBH) is unknown. Although different options have been proposed, involving, e.g. intermediate mass direct collapse BHs, BH remnants of massive stars remain the most natural explanation. To identify the most favourable conditions (if any) for their rapid growth, we study the accretion rate of a M = 100 M⊙ BH formed in a typical z = 10 galaxy under different conditions (e.g. galaxy structure, BH initial position, and velocity). We model the galaxy baryonic content and follow the BH orbit and accretion history for 300 Myr (the time span in 10 > z > 7), assuming the radiation-regulated accretion model by Park & Ricotti (2013 ). We find that, within the limits of our model, BH seeds cannot grow by more than 30 per cent, suggesting that accretion on light-seed models are inadequate to explain high-z SMBH. We also compute the X-ray emission from such accreting stellar BH population in the [0.5–8] keV band and find it comparable to the one produced by high-mass X-ray binaries. This study suggests that early BHs, by X-ray pre-heating of the intergalactic medium at cosmic dawn, might leave a specific signature on the H i 21 cm line power spectrum potentially detectable with SKA.